The Interpersonal Functions in the Batak Toba Traditional Wedding Speeches - Siahaan, Sanggam (Journal of English Teaching as a Foreign Language, 2016)
Interpersonal function is the languagefunction used to negotiatehuman experience such as abstract like love, anger,plan, etc. and concrete objectlike human, animal, place, etc. The native of speakers of languages use different structures of their linguistic features to create the language function. They structure their language to create different meaning in the context to negotiate those meanings or messages to their listeners The main problem explored is posted on the tacit knowledge of the Batak Toba people on how they create the interpersonal functions in the Batak Toba Traditional Wedding Speeches. The main theory used as the analytical framework is based on the interpersonal function (Halliday, 1994). The research is conducted based on a descriptive qualitative design in which the data are collected from a group of Batak Toba people who are delivering some wedding speeches in Balige, North Sumatera, Indonesia in December 2011. The data is collected and analyzedaccording to the concept of the concurrent activities of a naturalistic researcher, i.e., the data collection, reduction, display and drawing the conclusion(Miles and Huberman, 1984). The findings indicate that the native speakers the Batak Toba Language use logico-semantic relations to provide the propositions of future harmonic house-hold life and proposal for future of-spring, prosperity, dignity and health of the wed in the Batak Toba Society.